(untitled) (Journal of Environmental Science and Natural Resources, 2015)
In Bangladesh, flood and river erosion is a very common event and it has been occurred since 1988 and its process is till going on. The study was conducted in two char villages of the Jamuna River in the Bhuapur upazila of Tangail districts, namely Khanurbari and Shushua char from July to December 2011. The empirical data and findings were procured by the application of social survey, focus group discussion and field observation. The study explored the peoples indigenous survival techniques and assessed variation in peoples ability to adopt with floods and river erosion in those char villages. The result of the study showed that the people in char land with high flood proneness and low socio-economic circumstances were more likely to fail to adopt with impacts compared to people in areas with high and sudden flooding. The char people use their indigenous knowledge to adapt through this diverse situation. The study explores a negative fact that without any organizational support, the people of char have to formulate and undertake various adaptation techniques in their own way. Finally, the study recommended some suggestions for the policy planners and implementers for the future development of char areas in Bangladesh. It emphasizes the importance of the government and the non-governmental organizations to take their own responsibilities in the devastating situation of the flood and riverbank erosion. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22138 J. Environ. Sci. & Natural Resources, 7(1): 13-19 2014